Characterization of the biodistribution profile of a human Dialyzable Leukocyte Extract (hDLE) by in vivo fluorescence imaging: a strategy to infer the ADME profile of complex multipeptide drugs - Fragozo, Ana; Trejo-Martínez, Ismael; Domínguez-Bernal, Kuauhtémok; Valencia-Flores, Luis; Macias-Palacios, Zaira; Pavón, Lenin; Pérez-Torres, Armando; Aguilar-Alonso, Francisco A.; Vázquez-Leyva, Said; Vallejo-Castillo, Luis; Pérez-Tapia, Sonia Mayra (Frontiers in Pharmacology, 2026)
The immunomodulator Transferon Oral® (TO) is a human Dialyzable Leukocyte Extract (hDLE), id est, a complex mixture of peptides smaller than 10 kDa derived from human buffy coats. TO reduces TNF-α, IL-6, and IgE; and induces IFN-γ levels, which makes it useful in the treatment of allergies, autoimmunity, and infections. Its complex composition has made it difficult to characterize its pharmacokinetic profile, target organs, and mechanism of action. This study focused on describing the biodistribution profile of TO peptides indirectly using in vivo imaging. The TO peptides were coupled to the fluorophore Alexa 488 and administered intravenously (IV), subcutaneously (SC), intraperitoneally (IP), intramuscularly (IM), and oropharingelly (ORO) to female and male Crl: Nu-Foxn1nu Nu/Nu nude mice. It was verified that the TO peptides linked to the fluorophore maintained their biological activity (increment of survival in a murine model of HSV-1 infection) as a critical quality control. The fluorescence was acquired using an IVIS imaging system. Parenteral administration routes showed consistent biodistribution of TO peptides from the site of administration to the cervical and axillary areas, except for the IM route, where no biodistribution pattern was observed. The IV route of administration reached maximum fluorescence the fastest, at 15 min, and the peptides remained in the study subjects for around 180 min in all routes. Interestingly, the TO peptides were absorbed via ORO and exhibited a biodistribution pattern similar to that of the parenteral routes. Elimination via glomerular filtration was observed for all administration routes, and accumulation of TO peptides in the axillary and lymph nodes, as well as the heart, was confirmed by ex vivo analysis. The results of this work are relevant because they identify how the peptide components of an hDLE are absorbed enterally and parenterally and consistently accumulate in immunologically relevant organs where they exert their immunomodulatory function. Furthermore, it sets the first precedent for indirectly describing the absorption, distribution, metabolism, and excretion processes of a drug composed of a myriad of molecules using in vivo imaging.